Ethical Commitment to Women’s Participation in Transitional Justice - Elisabeth Porter (Global justice: Theory, Practice, Rhetoric, 2013)
Ethical issues of justice and human rights are central to countries emerging from conflict. Yet involving women in transitional justice processes rarely is articulated in ethical terms. To make a case for an ethical commitment to improving women’s participation in these processes, the paper begins by exploring why transitional justice strategies should bother with gender. Women and men often experience conflict and injustices differently which may require different responses to redress harms suffered. Timor-Leste is used as a case study. The paper explores whether hybrid traditional and formal justice systems can address women’s justice claims in principle and specifically, when applied to Timor-Leste. The paper maintains that customary justice practices can be combined with conventional ones, but only when both practices adhere to international human rights conventions, which rarely happens where patriarchal practices are entrenched. The conclusion addresses what might be done to create gender-responsive justice systems given that they are crucial in building environments that are conducive to sustainable peace and security.